Impact of dividend policy on the shareholders’ wealth: Shariah vs non-Shariah companies listed in Bursa Malaysia / Farazida Mohd Akit and Nor Haliza Hamzah - Mohd Akit, Farazida; Hamzah, Nor Haliza (Arshad Ayub Graduate Business School, 2014)
The purpose of this study is to examine the impact of dividend policy on the shareholders’ wealth of Shariah and non-Shariah compliance companies listed in Bursa Malaysia main market. A sample of 274 Shariah compliance companies and 129 non-Shariah compliance companies listed on Bursa Malaysia for the period of 2004 to 2013 has been selected for this study. The results are obtained through two-way fixed-effect Generalized Least Squares (GLS) regression for Shariah compliance companies and random-effect GLS regression for non-Shariah compliance companies. The identified determinants are dividend per share (DPS), retained earnings per share (REPS), return on equity (ROE), lagged price earnings ratio (PER,_|), financial leverage (DTE) and firm’s size (InTA). The results indicates that the measurements for dividend policy (DPS and REPS) are significant determinants of shareholders’ wealth for both Shariah and non-Shariah compliance companies. On the other hand, it is revealed that financial leverage is an influential determinant of shareholders’ wealth for Shariah compliance companies but not for non-Shariah companies.